2010
DOI: 10.1186/1475-2875-9-372
|View full text |Cite
|
Sign up to set email alerts
|

Is staying overnight in a farming hut a risk factor for malaria infection in a setting with insecticide-treated bed nets in rural Laos?

Abstract: BackgroundOvernight stays in farming huts are known to pose a risk of malaria infection. However, studies reporting the risk were conducted in the settings of poor net coverage. This study sought to assess whether an overnight stay in a farming hut is associated with an increased risk of malaria infection if insecticide-treated bed nets (ITNs) are properly used.MethodsA pair of cross-sectional surveys was carried out in the Lamarm district of Sekong province, Laos, in March (dry season) and August (rainy seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…As per the World Malaria Report 2011 [1], 96% of those who possess a net actually sleep under it. Some of the reasons provided by some of Bhutaneses for not sleeping under a net, which were consistent with other studies [38], were that people do not sleep at home as they guard their crops during harvest seasons; additional nets have to be supplied to meet such practices [39,40]. …”
Section: Discussionsupporting
confidence: 80%
“…As per the World Malaria Report 2011 [1], 96% of those who possess a net actually sleep under it. Some of the reasons provided by some of Bhutaneses for not sleeping under a net, which were consistent with other studies [38], were that people do not sleep at home as they guard their crops during harvest seasons; additional nets have to be supplied to meet such practices [39,40]. …”
Section: Discussionsupporting
confidence: 80%
“…When household size increases, bed nets are not properly used. Evidence has shown that people sharing a bed net with more than five people are more likely to have malaria than those sharing a bed net with up to two people [ 89 ]. The districts with the highest average number of persons per bedroom are Nyagatare, Ngoma and Bugesera.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, their exposure to vector mosquitoes is increased. Among the ethnic minorities and forest fringe inhabitants, adult males in particular report that they stay in the forest overnight to hunt or collect wood [ 3 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Lao PDR achieved a >75 % decrease in the incidence of malaria between 2000 and 2015. However, asymptomatic infections continue to be detected in rural, remote villages [ 7 , 9 , 10 ], which contributes to on-going local transmission. Asymptomatic carriers are not detected by the current national surveillance system, which is based on passive case detection at healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%